Sultan of the wise / Secretary of State / Hibat Allah ibn al-Talmid (d. 560 A.H. 1164 A.D.) (Journal of the College of Basic Education, 2022)
In the Abbasid era, medicine became one of the important mental sciences that received great attention and care.by the Abbasid caliphs, and perhaps the reason for that is the large number of Arab Islamic conquests thatIt helped the Arabs to get acquainted with different cultures, which increased their understanding and knowledge of the importance of sciences.on the one hand, and on the other hand, the flourishing of the translation movement, which also helped toTranslating many books of the Greeks, Romans, Indians, Egyptians and others, which helped flourish the science of